Balance And Unbalance As Urban Technique For Interpretation Of Old Parts of Cities - حسن هاشم, باقر (Journal of Planner and Development, 2005)
the study aimed to drive and test an urban technique from \"balance and unbalance concept\" in physical structure of old parts of cities depending on \"supply and demand system \" Detailed survey has been achieved to define architectural units patterns and urban functions that occupied it .